Influence of Leadership on Employee Motivation in PT. Asuransi Jasa Raharja Putera Jakarta - Jaka Santosa (Kusuma Negara Business School, 2020)
Leadership is a way for a leader to influence the behavior of his subordinates, so they are willing to cooperate and work productively to achieve the goals set. A leader requires motivating skills, so that the role of leadership in motivating others or specifically can be realized in the bond of togetherness. Employees with high work motivation will work with passion, discipline, initiative and with an awareness of their obligations to work more effectively and efficiently. This study aims to determine the effect of leadership on employee motivation at PT. Asuransi Jasa Raharja Putera Jakarta. The sample used is Simple Random Sampling, said to be simple because the sampling of members of the population is done randomly without regard to the strata that exist in that population and also uses a Likert scale. The research methods used were observation, interviews, questionnaires, and documentation. Based on the data obtained below is a summary of the calculation results using SPSS 25. The correlation coefficient value 0.837 means that it is very strong and has a relationship between leadership and work motivation, the results of the coefficient of determination of 70.0% and the remaining 30.0%% of other factors , the results of the regression equation Y = 6.117 + 0.841 X, it means that each increase in unit X increases by about 0.841.